Mixed-methods evaluation and behavior change interventions to improve hand hygiene resources and practices among healthcare workers in polyclinics and health centers in Belize, 2023 - Anh N. Ly; Kelsey McDavid; Christina Craig; Rosalva Blanco; Vickie Romero; Melissa Diaz-Musa; Francis Morey; Russell Manzanero; Gerhaldine Morazan; Makenzie Towery; Anna Impellitteri; Matthew Lozier; et al. (PLoS ONE, 2025)
Background Hand hygiene (HH) is an effective public health measure to prevent the spread of infections in healthcare settings. A previous study in Belize showed gaps in HH practices in hospitals and large polyclinics; however, there are limited national data assessing access to and use of HH resources in smaller outpatient primary care facilities, especially in rural areas. Methods In February 2023, facility assessments were conducted at 26 health centers and polyclinics in Belize to assess the availability of HH resources. Of these, 12 pilot healthcare facilities (HCF) were selected for additional evaluation, which included observation of HH practices, hand dirtiness assessments, and in-depth interviews. Following the evaluation, a six-week (August – September 2023) hand hygiene champion intervention was implemented at the 12 pilot HCFs to promote HH practices. Follow-up assessments were conducted during September – November 2023 to evaluate the impact of the intervention. Descriptive statistics and adjusted odds ratios were calculated to assess HH resources, adherence, and dirtiness. Thematic analysis was conducted for the in-depth interviews. Results Most (87%) patient care rooms at the HCFs had either a handwashing station with soap and water or a functional alcohol-based hand rub dispenser. Following the intervention, there was a significant increase in hand hygiene adherence (HHA) among healthcare workers (aOR = 4.21; 95% CI = 2.70, 6.56). Overall, HHA was more common during invasive procedures (aOR = 1.82; 95% CI = 1.07, 3.09) and after patient contact (aOR = 1.68; 95% CI = 1.12, 2.52). The median hand dirtiness score increased from 8 to 9, indicating less visible debris. In-depth interviews found that healthcare workers viewed the intervention as a helpful reminder but encountered challenges such as having few staff, lack of time, and lack of resources during program implementation. Conclusion The observed increase in HHA and positive feedback from healthcare workers suggests that a peer-led program may be an effective strategy to improve HHA in HCFs. Future programs may consider tailoring the intervention to the resource and adherence gaps observed at each facility to increase impact.